METHOD FOR USING SOLAR ENERGY TO GENERATE CLEAN ENERGY BASED ON VACUUM-ATMOSPHERIC POWER AMPLIFICATION TECHNOLOGY (World Science, 2020)
New method of converting solar energy into useful work and generating clean energy based on the technology of vacuum-atmospheric power amplification has been developed. As an energy source this technology uses an external supply of potential energy of the atmosphere in the Earth's gravitational field, which exists everywhere and becomes useful when it is converted into the desired form for use.In this case, clean energy is generated in the same way as in hydroelectric power plants. The main advantage of the proposed method is that the devices in which it is used generate energy stably, regardless of the time of day, weather and location. Clean energy absorbed from the atmosphere is independently generated with any necessary design capacity for a specific consumer in the desired location without the use of organic fuel and main power grids. The article presents a theoretical justification of the method of generating clean energy based on the VAPA technology. Examples of using this method in various devices are given.